Negation in Ngor-Okpala dialect of Igbo - Nwachukwu, Emmanuel Lucas Nwachukwu (Journal of Literature Language and Academic Studies, 2023)
Negation is a morpho-syntactic operation that exist every human natural language and is sine-qua-non for everyday human communication. As a universal linguistic phenomena used in everyday conversation, it is poorly captured in Ngor-okpala dialect of Igbo. Some notable scholars like Uba-Mgbemena (1981), Ndimele (1995, 2004), Obiamalu (2004) and Onuora (2017) have written on negation in Igbo without considering the differences with reference to dialectal variation within the Igbo language. This study aims at reviewing negation in Ngor-okpala dialect of the Igbo language and how negative markers (fu,-m, la, and ghi,) are unique to Ngor-okpala dialect and used in various constructions. The study will review how these various negative markers in Ngor-okpala dialect have morpho-semantic impacts, the study also highlight some functions of negation in the linguistic framework of Ngor-okpala dialect. The study adopts the Optimality theory to investigate the underlying issues in the study. The study adopts descriptive analysis and data for the study were gathered from both primary sources such personal communications and secondary sources such as journal articles, Youtube videos and textbooks. Findings reveal that Ngor-okpala dialect has its unique negative markers which are used in everyday communication to convey contradiction, opposition, or disagreement of previously stated assertions. The study also revealed the various forms of negation such as ghi, la, fu, -m, are suffixation of different forms to simple verb root and sometimes to a verb root that has already taken an extensional affix. The study therefore concludes that suffixation of different negative markers such as ghi, la, fu to verb root are unique forms negation in Ngor-okpala, and they exist both at the, morphological and semantic levels, which impacts on the structure and meaning of any expression in the dialect.